Effect of glycemic control and dyslipidemia on plasma vascular endothelial growth factor and pigment epithelium-derived factor in diabetic retinopathy patients in Northern Nigeria - Unung, Paulinus Jimmy; Bassey, Iya Eze; Etukudo, Maisie Henrietta; Udoh, Alphonsus Ekpe; Alhassan, Mahmoud B; Akpan, Uwem Okon (International Journal of Health Sciences, 2020)
Objectives: The disruption of the reciprocal regulation between vascular endothelial growth factor (VEGF) and pigment epithelium-derived factor (PEDF) has been associated with the pathogenesis of diabetic retinopathy (DR). This study assessed the levels of VEGF, PEDF, indices of glycemia, and lipid profile in diabetic patients with retinopathy. Methods: One hundred fifty participants comprised 50 type 2 diabetic patients with DR, 50 without DR and 50 non-diabetic normotensive controls, aged 30–80 years, were randomly recruited for this case-control study. The study was carried out from November 2017 to December 2018. VEGF, PEDF, glycated hemoglobin (HbA1c), fasting plasma glucose, and lipid profile were determined using standard methods. Blood pressures (BP) and anthropometric indices were measured. Chi-squared test of independence, analysis of variance, and Pearson’s correlation were used to analyze data. Statistical significance was set at P < 0.05 and 95% confidence interval. Results: Both diabetic groups had significantly higher (P = 0.001) systolic and diastolic BP, VEGF, PEDF, HbA1c, fasting plasma glucose, triglycerides, total, high-density lipoprotein-cholesterol (HDL-C), and low-density lipoprotein-cholesterol (LDL-C) levels and significantly lower (P = 0.005) VEGF/PEDF than the controls. However, the diabetics with retinopathy had significantly higher (P = 0.001) HDL-C, LDL-C, VEGF, and PEDF levels compared to the diabetics without retinopathy. There were no significant differences (P > 0.05) in the levels of VEGF, PEDF, and VEGF/PEDF in both groups of diabetics that had good glycemic control and poor glycemic control. There was also no significant difference (P > 0.05) in the levels of VEGF and PEDF between the dyslipidemic and non-dyslipidemic subjects in both diabetic groups. Conclusion: DR is associated with higher levels of VEGF and PEDF while good glycemic control and dyslipidemia seem not to have a profound effect on VEGF and PEDF levels in diabetics with or without DR. Higher PEDF levels are associated with higher atherogenic risk in the diabetics with retinopathy.